2014
DOI: 10.1186/1471-2431-14-247
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of positive and negative parenting behaviours: evidence from the ALSPAC cohort

Abstract: BackgroundThis study aimed to establish the predictors of positive and negative parenting behaviours in a United Kingdom population. The majority of previous research has focused on specific risk factors and has used a variety of outcome measures. This study used a single assessment of parenting behaviours and started with a wide range of potential pre- and post-natal variables; such an approach might be used to identify families who might benefit from parenting interventions.MethodsUsing a case-control subsam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
2
26
2
1
Order By: Relevance
“…We found that boys scored higher on their perceived parental and grandparental Indifference and Overprotection , and than did girls, which was inconsistent with previous findings that girls more than boys experienced their parents as demanding (a close relative of Overprotection) and boys experienced their parents as more intrusive (contrary to higher Indifference) (Thomson et al 2014; Elstad and Stefansen 2014). Furthermore, girls perceived more grandparental overprotection in our study, inconsistent with a previous study that showed granddaughters had closer relationships with their grandparents (Hyde and Gibbs 1993).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that boys scored higher on their perceived parental and grandparental Indifference and Overprotection , and than did girls, which was inconsistent with previous findings that girls more than boys experienced their parents as demanding (a close relative of Overprotection) and boys experienced their parents as more intrusive (contrary to higher Indifference) (Thomson et al 2014; Elstad and Stefansen 2014). Furthermore, girls perceived more grandparental overprotection in our study, inconsistent with a previous study that showed granddaughters had closer relationships with their grandparents (Hyde and Gibbs 1993).…”
Section: Discussioncontrasting
confidence: 99%
“…Early studies found gender differences in parent-child relationships and parenting behaviors. Thomson et al (2014) found that mothers with female infants had fewer negative interactions with them. Further, Elstad and Stefansen (2014) showed that more girls experienced their parents as being demanding than did boys, while boys experienced their parents being more intrusive.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of these approaches of parenting are important because they have implications on development throughout the lifespan (Thomson et al 2014). A number of parenting approaches exist in the literature (Wood et al 2003;Aunola and Nurmi 2005) that were categorized into positive and negative parenting approaches for the purposes of this review.…”
Section: Understanding Parenting Approaches and The Relationship Withmentioning
confidence: 99%
“…Parenting has a number of interacting factors (such as personal stresses or societal demands) that could play a role in their approaches to parenting (Belsky 1984;Thomson et al 2014). Of interest have been the effects of parenting on the development of parent-child relationships (Aunola and Nurmi 2005;Chan and Koo 2011;Betts et al 2013;Arnett 2014).…”
Section: Understanding Parenting Approaches and The Relationship Withmentioning
confidence: 99%